Syncope: driving advice is frequently overlooked. Issue 851 (September 1996) - MacMahon, M.; O'Neill, D.; Kenny, R. A.
Abstract : Consecutive referrals to a syncope clinic were asked about the frequency of enquiries about driving status by referring general practitioners and/or hospital specialists. Although 40% were drivers, only 13% of patients had been previously asked about driving, and 12% of drivers had experienced symptoms whilst driving. This represents an important oversight on the part of referring doctors.